Niveles de comprensión lectora en estudiantes de quinto grado de secundaria de la institución educativa Nº 60756 del distrito de Iquitos 2023 - Muñoz Nina, Edson Gabriel (2025)
The main objective of this study was to understand how fifth-grade secondary school students at Educational Institution No. 60756 in the district of Iquitos are understanding texts during the year 2023. To this end, a questionnaire was administered to 132 students and record sheets on their learning achievements were also reviewed. The approach was descriptive, with a field-based, cross sectional, and non-experimental design. Upon analyzing the results, it was found that the majority of students were at an intermediate level of reading comprehension (40.82%), followed by 37.41% at a high level and 21.77% at a low level. This same pattern was confirmed when reviewing the record sheets, where 51.02% also fell into an intermediate level.